KEANEKARAGAMAN JENIS BURUNG DI DESA LORULUN KECAMATAN WERTAMRIAN KABUPATEN KEPULAUAN TANIMBAR - Grainlove G. Tuhurima; Cornelis K. Pattinasarany; Fanny Soselissa (MARSEGU : Jurnal Sains dan Teknologi, 2026)
This study aimed to identify bird species diversity and examine its relationship with habitat characteristics in Lorulun Village, Wertamrian District, Tanimbar Islands Regency. The research was conducted from March to April 2024 using field observations. Bird data were collected using the line transect method, while vegetation data were analyzed using a combination of line and plot sampling methods. Observations were carried out in three observation blocks, each covering one hectare. The results showed that 20 bird species belonging to 15 families were recorded, with a Shannon–Wiener diversity index (H′) value of 2.402, indicating a moderate level of species diversity. Vegetation diversity and complex habitat structure played an important role in supporting bird presence and activity. The occurrence of endemic and conservation-priority species highlights the importance of sustainable habitat management to maintain bird diversity and ecosystem balance.